One-pot synthesis of silica monoliths with hierarchically porous structure - Drisko, Glenna L. (2012)
Poly(furfuryl alcohol) (PFA) and block copolymer Pluronic F127 were used as pore templates to create mechanically robust silica monoliths with a hierarchical and interconnected macro?mesoporous network in an easy, reproducible bimodal scale templating process. Control over the morphology was obtained by varying the reactant ratios. Phase separation on the submicrometer scale occurred when furfuryl alcohol was cationically polymerized and therefore became immiscible with the solvent and the silica precursor. Upon a subsequent sol?gel reaction, a silica-F127 matrix formed around the PFA spheres, leading to macropore structures with mesoporous walls. Surface areas of the final structures ranged from 500 to 989 m2/g and a maximum pore volume of 4.5 mL/g was achieved. Under mildly acidic conditions, micelle-templated mesopores resulted. Interconnected macropores could be obtained by increasing the pH or the block copolymer concentration. The formation mechanism and the relationship between PFA, Pluronic F127 and acidity are discussed in detail.